Analisis Efektivitas Kebijakan Anti-Korupsi Di Indonesia: Studi Pada Kasus Penanganan Korupsi Di Sektor Publik - Yuningsih, Henny; Munawir, Munawir (Lex Librum : Jurnal Ilmu Hukum, 2024)
Corruption is a major challenge in national development that negatively impacts the economy, political stability, and the welfare of society. This research analyses the effectiveness of anti-corruption policies in Indonesia, particularly in handling corruption cases in the public sector. This study uses a qualitative approach with secondary data analysis, including reports from anti-corruption agencies, legal studies, and government documentation. Anti-corruption policies in Indonesia significantly reduce corrupt practices, but they are not yet fully effective. The main obstacles include weak law enforcement, a lack of competent human resources, and insufficient coordination between the involved agencies. Moreover, the still strong culture of corruption and political influence often hinders the consistent implementation of policies. This research suggests increased transparency, stronger regulations, and deep institutional reforms to make anti-corruption policies more effective. With the synergy between agencies and community support, it is hoped that the efforts to eradicate corruption in Indonesia can increase public trust and create good governance in the public sector.